The Effects of the Current Global Economic and Financial Crisis on the EU Budget - Adina DORNEAN; Andreea SANDU (Transylvanian Review of Administrative Sciences, 2013)
The aim of this paper is to analyze the main effects of the current global financial and economic crisis on the European Union budget and the measures that were taken in order to support the EU member states with the purpose of limiting and counteracting its effects. The focus will be on the budgetary expenditure and on the new Treaty on Stability, Coordination and Governance. For this purpose, we developed a regression model using the Least Square method with three significant variables: a dependent variable – EU budgetary expenditure and two independent variables – budgetary deficit and unemployment rate of member states. According to our analysis, the crisis determined the increase of the EU budgetary expenditure, which was due especially to the increase of the budgetary deficit and rising unemployment in the EU member states. Our findings suggested that the budgetary deficit and the unemployment rate had a highly significant influence on community expenditure growth during the crisis, while the GDP growth and the public debt did not have any significance for the community expenditure growth.